A new species of the genus Chrysacris Zheng, 1983 from China (Orthoptera: Acridoidea, Acrididae) - Cao, Cheng-Quan; Shi, Jian-Ping; Yin, Zhan (Zootaxa, 2017)
The Chrysacris Zheng, 1983 is a median genus in Acrididae, which contains 18 species [Tu & Cheng, 1964; Zheng, 1983; Lian & Zheng, 1987; Li & Chen, 1988; Zheng, 1988; Liu, 1990; Ren et al, 1991; Liang & Jia, 1992; Zheng et al, 1992; Ren et al, 1993; Zhang & Zheng, 1993; Zheng, 1993; Zheng & Shi, 1993; Niu, 1994; Ren et al, 1994; Zheng et al, 1995; Yin et al, 1996; Ren 2001; Ren et al, 2002; Yin et al, 2003; Zheng et al, 2011; Dong et al, 2015; Eades, et al, 2017; Zhang et al, 2017], mainly distributed in Heilongjiang, Jilin, Liaoning, Inner Mongolia, Shanxi, Shaanxi, Henan and Guizhou provinces of China. A new species of the genus Chrysacris is described from Inner Mongolia, China in this paper. Type specimens are deposited in the Natural Museum of Hebei University, Baoding, Hebei, China.